How Third World rural households adapt to dietary energy stress: the evidence and the issues - Payne, Philip; Lipton, Michael (International Food Policy Research Institute, 1994)
People can adjust to environmental changes by calling on a wide range of physical attributes, capabilities, and behaviors. For survival, probably the most important are those that make it possible to prevent serious imbalances between food energy needs and the amount of food that can be acquired at acceptable cost. Those who formulate food and agricultural policies need to know the scope, costs, and benefits of the more common adaptive strategies used by poor people, who are normally at greatest risk of energy stress. In particular, policymakers and analysts need to assess the scope and limits of adjustments by individuals or groups. When might adjustments fail to be biologically adaptive, that is, to reduce the risk that adverse effects of undernourishment will prevent individuals from contributing to the genetic inheritance of future generations? Even if adjustments are biologically adaptive, when are they likely to involve unacceptable suffering, damage to health, or social incapacity? In How Third World Households Adapt to Dietary Energy Stress: The Evidence and the Issues, IFPRI Food Policy Review 2, Philip Payne and Michael Lipton draw upon relevant literature from a range of subjects spanning the biological, behavioral, and social sciences and set out a conceptual framework to identify the current state of knowledge--and the gaps in it.